Pengaruh Sosialisasi Perpajakan Dan Literasi Digital Terhadap Pemahaman Pelaporan Pajak Pada Kalangan Gen Z - Jonathan Kirana Siadari; Siti Zikriyah; Gita Adelia; Linawati Linawati (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the influence of tax socialization and digital literacy on the understanding of tax reporting among Generation Z in South Tangerang. The study used a quantitative approach with 100 respondents selected through a purposive sampling technique. Data were collected using a Likert-scale questionnaire and then analyzed through validity and reliability tests, multiple linear regression, and t- and F-tests using SPSS. The results showed that tax socialization had a significant effect on the understanding of tax reporting. Digital literacy also had a significant influence and was the most dominant factor in improving Generation Z's ability to understand the digital-based SPT reporting process. Simultaneously, the two variables explained 66.4% of the variation in understanding of tax reporting. These findings emphasize the importance of effective socialization strategies and increasing digital literacy to support tax compliance in the digital era.